Perspectives of community-dwelling older adults with chronic diseases on Baduanjin practice: A qualitative study - Haixu Ji; Wei Li; Jinhua Zhang; Xuyan Liu; Jing Wang; Guanglei Dong (PLoS ONE, 2026)
Background With the accelerating aging of China’s population, Baduanjin has been promoted as a community-based exercise to enhance public health, particularly among older adults with chronic diseases. As a traditional Chinese exercise with a long history and profound cultural connotations, Baduanjin has attracted a large number of practitioners. However, the factors underlying the sustained practice of Baduanjin remain insufficiently explored. Objective This study aims to explore the factors underlying the persistence of older adults with chronic diseases in practicing Baduanjin. Methods A qualitative research approach was adopted in this study. 25 practitioners participated in semi‑structured face‑to‑face interviews. Thematic analysis was employed to analyze the data and generate core themes. Results The factors driving community-dwelling older adults with chronic diseases to persist in practicing Baduanjin were analyzed across five dimensions: perceived safety and learning-practice ease, improvements in physical health, promotion of mental well-being, enhancement of social functioning, and appreciation of traditional culture. Conclusion Community-dwelling older adults with chronic diseases maintain long-term Baduanjin practice not only due to its perceived safety and ease of learning and practice, but also because it embodies the essence of traditional Chinese culture. Moreover, regular practice contributes to improved physical health, promoted mental well-being, and enhanced social functioning in this population. Accordingly, Baduanjin shows considerable potential as a community-based exercise intervention to support health promotion among community-dwelling older adults with chronic diseases.